Pengaruh Komunikasi Antar Budaya Dan Penanganan Keluhan Pelanggan Terhadap Loyalitas Pelanggan - Itsqon Wafi Fauzan; Hanna Maria Siagian; Muhammad Baihaqi; Putri Yuliarman; Sri Ningsi Karnance (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine and examine the effect of intercultural communication variables and handling customer complaints on customer loyalty. This research uses quantitative research methods. Data collection in this study was obtained through distributing questionnaires to buyers at MMTC Fruit Market. The sample in this study amounted to 100 respondents. The sampling technique used is non probability sampling. The data analysis used in this study used multiple linear regression. The results of this study concluded that intercultural communication has no partial effect on customer loyalty, with the t test results 0.970 < 1.984 with a significance value of 0.334 > 0.05. Handling customer complaints partially has no effect on customer loyalty, at a significance value of 0.590> 0.05 and a calculated t value of -0.570 < 1.984. Meanwhile, based on the F test that intercultural communication and handling customer complaints have no simultaneous effect on customer loyalty with a sig value of 0.520> 0.05 and a calculated f value of 0.658 < 3.09.